Dinamika Kinerja Keuangan Perusahaan di Sektor Kesehatan, Keuangan, dan Teknologi - Breliastiti, Ririn; Nelson, Catheryn Iona; Daynarra, Babyrra; Sutanto, Kevin Amadis; Claudia T., Stephany (Media Ilmiah Akuntansi, 2024)
This study explores the financial performance comparison of three major service sectors: healthcare, finance, and technology, with a focus on liquidity, solvency, activity, and profitability. Using data from 2021 and 2022, the study aims to provide in-depth insights into the financial strengths and weaknesses of each sector during the Covid-19 pandemic period. The analysis involves comparing the financial ratios of selected companies within each sector to industry averages to identify trends, differences, and potential issues. The results show that the healthcare sector has the highest liquidity, solvency, and profitability among the three sectors. The finance sector demonstrates the highest operational efficiency compared to the other two sectors but has the lowest liquidity, solvency, and profitability. The technology sector shows adequate liquidity, solvency, and profitability but lacks efficiency in its operations. Future strategies for the healthcare sector should include diversifying investments, optimizing operations, and enhancing customer service. For the finance sector, strategies should focus on improving liquidity and solvency, innovating in products and services to boost profitability. The technology sector should invest in automation, human resource development, and maintain a strong focus on innovation.